A pregnancy with GDM, hypothyroidism, polyhydrramnios with history of treatment for subfertility - Mukherjee, Soumya; Sen, Sukanta; Misra, Sukanta (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Gestational diabetes (GDM) is defined as carbohydrate intolerance that begins or is first recognized during pregnancy. Although it is a well-known cause of pregnancy complications, its epidemiology has not been studied systematically. There are several identifiable predisposing factors for GDM, and in the absence of risk factors, the incidence of GDM is low. Low thyroid hormone levels in early pregnancy are a risk factor for GDM incidence. Although gestational hyperthyroidism is uncommon (0.2%), hypothyroidism (autoimmune disease or suboptimal iodine intake) occurs in 2.5% of women and is predictive of reduced neonatal and child neuropsychological development and maternal obstetric complications. It is well documented that thyroid disorders are associated with maternal and fetal complications during gestation and sequelea after delivery. The case-finding strategy does not solve the serious problem of leaving undiagnosed and untreated patients without risk factors. In the absence of strong evidence that support universal thyroid screening in pregnancy, current guidelines suggest a case-finding approach targeting thyroid function testing in high-risk groups. A couple have history of sub-fertility. Patient conceived following treatment. During pregnancy, GDM developed and later half of pregnancy was complicated by polyhydramnios. Baby was delivered by LSCS due to PPROM.